Amoebiasis: Etiologi, patofisiologi, morfologi, diagnosis, dan pengobatan - Jannah, Insani Fitrahulil; Abdullah, Asriyani (Indonesian Journal of Health Science, 2025)
Amoebiasis is an infectious disease caused by Entamoeba histolytica and remains a public health concern, especially in developing countries with poor sanitation. Transmission occurs via the fecal–oral route through contaminated food, water, or hands. The infection may be asymptomatic or progress to severe forms such as dysenteric colitis and amoebic liver abscess. Traditional diagnosis relies on stool microscopy, which has limited sensitivity and specificity. Molecular diagnostics such as PCR and immunological methods like ELISA have improved diagnostic accuracy but are not widely accessible in endemic regions. Treatment varies according to disease severity, involving luminal amebicides for non-invasive infections and tissue amebicides for invasive disease. Long-term prevention requires improved sanitation, public education, and vaccine development. Future research should focus on host–parasite interactions, gut microbiota dynamics, and the identification of biomarkers and novel therapies to enable more effective and sustainable control of amoebiasis in affected populations. Amoebiasis adalah penyakit infeksi yang disebabkan oleh Entamoeba histolytica, dan masih menjadi masalah kesehatan masyarakat di negara berkembang dengan kondisi sanitasi yang buruk. Penularan terjadi melalui jalur fekal-oral, baik secara langsung maupun tidak langsung. Infeksi ini dapat bersifat asimtomatik atau menyebabkan gejala berat seperti kolitis disenterik dan abses hati amebik. Diagnosis tradisional mengandalkan pemeriksaan mikroskopis feses, meskipun teknik ini memiliki keterbatasan dalam sensitivitas dan spesifisitas. Kemajuan dalam diagnostik molekuler seperti PCR dan metode imunologis (ELISA) telah meningkatkan akurasi diagnosis, namun aksesnya masih terbatas. Pengobatan tergantung pada tingkat keparahan infeksi, dengan penggunaan amebisida luminal untuk infeksi non-invasif dan amebisida jaringan untuk infeksi invasif. Pencegahan jangka panjang melibatkan peningkatan sanitasi, edukasi masyarakat, dan pengembangan vaksin. Penelitian masa depan harus difokuskan pada interaksi parasit-inang, peran mikrobiota usus, serta penemuan biomarker dan terapi baru untuk pengendalian amoebiasis yang lebih efektif dan berkelanjutan.